Avaliação histométrica do processo de reparo em defeitos de calvária de ratos com membrana de PCL e membrana de colágeno porcino - Francati, Tamires Melo [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The use of membranes that help in the process of guided bone regeneration (GBR) is also an aspect of the study of biomaterials compatible that assist in the process of repair. Still in a study phase membrane developed at the University of San Carlos is based on nano polycaprolactone (PCL) fibers which is a biodegradable polymer with a rhythm is controllable degradation, maintaining the structure during a longer period of cell growth. The objective of this project was to evaluate by means of histological analysis the potential to aid in bone neoformation PCL membrane with 5% of HA and porcine membrane in the process of critical bone defects repair in rat calvarium. 36 rats were used for histological analysis of critical defects in rat calvarium in times of 7, 30 and 60 days divided into three groups: G1: Blood clot, G2: Porcine embrane, G3: PCL. Histological analysis showed that the PCL membrane has a biological behavior with the fabric since it was not verified foreign body reaction in any specimen, it was also possible to verify that it allowed the GBR occurred both to 30 about the 60 days, and in some specimens it was verified the complete closure of the defect. The PCL membrane proved to be biocompatible with the potential to assist in the processes of GBR

O uso de membranas que auxiliem no processo de regeneração óssea guiada (ROG) é também uma vertente dos estudos de biomateriais compatíveis que auxiliam nesse processo de reparo. Membrana de polímero biodegradável, desenvolvida recentemente, que apresenta como base nano fibras de policaprolactona (PCL), com um ritmo controlável de degradação, mantém a estrutura durante um maior período do crescimento celular. O objetivo deste projeto foi avaliar por meio da análise histológica o potencial de auxiliar na neoformação óssea da membrana de PCL com 5% de HA e da membrana porcina no processo de reparo de defeitos ósseos críticos em calvária de ratos. Foram usados 36 ratos para análise histológica nos tempos de 7, 30 e 60 dias divididos em três grupos: G1: Coágulo, G2: Membrana Porcina, G3: PCL. Na análise histológica a membrana de PCL apresentou bom comportamento biológico com os tecido, pois não foi verificado reação de corpo estranho e nem reações inflamatórias, também foi possível verificar que a mesma permitiu que a ROG ocorresse tanto aos 30 quanto aos 60 dias, sendo que em alguns espécimes foi verificado o fechamento completo do defeito crítico. Concluiu-se que a membrana de PCL mostrou-se biocompatível com potencial para auxiliar nos processos de ROG
Keywords: Regeneração óssea guiada; Materiais biomédicos; Crânio; Ratos; Polímeros; Guided bone regeneration